PEDIATRIC APPENDICITIS: AGE DOES MAKE A DIFFERENCE - Aneiros,Belén (2019)
ABSTRACT Objective: To investigate the influence of patient age on the diagnosis and management of appendicitis, as well as to evaluate the rate of complications according to the age group. Methods: We undertook a retrospective analysis of 1,736 children who underwent laparoscopic appendectomy in our center between January 2000 and December 2013. Patients were divided in groups taken into account their age: group A were infants, group B were preschoolers, group C were those ones older than five years old, and group D were those ones younger than five years old. A p value of 0.05 was considered statistically significant. Results: We found higher incidence of misdiagnosis and atypical symptoms in the youngest patients. The rate of perforation was similar between group A and B (p=0.17). However, it was higher in group D than in group C (p<0.0001). The incidence of postoperative complications was higher in the youngest patients too (p=0.0002). Conclusions: The age does make a difference in acute appendicitis. Because of its unusual presentation in children younger than five years old, it is often misdiagnosed, which leads to an increased morbidity. Although clinical presentation varies between infants and preschoolers, no statistically significant differences were observed in the rate of perforated appendix or postoperative complications.